The Legal Status of Refugees as Perpetrators of Criminal Acts in the Indonesian Criminal Justice System - diva pitaloka (Jurnal Paradigma Hukum Pembangunan, 2026)
The presence of foreign refugees in Indonesia raises various legal issues, one of which is when refugees commit crimes within Indonesian territory. Although Indonesia has not ratified the 1951 Convention Relating to the Status of Refugees and the 1967 Protocol Relating to the Status of Refugees, refugee management remains guided by Presidential Regulation Number 125 of 2016 concerning the Management of Refugees from Abroad and applicable national legal provisions. This study aims to analyze the legal status of refugees as perpetrators of crimes within the Indonesian criminal justice system and examine the forms of criminal liability that can be imposed on them. The study uses a normative juridical method with a statutory, conceptual, and case approach. The legal materials used include laws and regulations, international legal instruments, scientific literature, and relevant court decisions. The results show that refugee status does not eliminate criminal liability for crimes committed within Indonesian territory. Refugees remain subject to national criminal law provisions based on the territorial principle. However, there is no comprehensive regulation regarding the handling mechanism for refugee perpetrators of criminal acts, particularly regarding coordination between law enforcement officials, immigration authorities, and international organizations. This situation has the potential to create legal uncertainty in the law enforcement process and in determining refugee status after serving a sentence. Therefore, harmonization of national regulations with the principles of international refugee law is necessary to ensure legal certainty, human rights protection, and the effectiveness of the criminal justice system in Indonesia.